Two level uncapacitated facility location problem with disruptions. (November 2019) - Ramshani, Mohammad; Ostrowski, Jim; Zhang, Kaike; Li, Xueping
Highlights: We study the two level uncapacitated facility location problem with disruption uncertainty. We formulate an integer nonlinear programming model. We develop Tabu search algorithm and a route subset selector heuristic method. We present computational results to evaluate the performance of the proposed algorithms. Abstract: Uncapacitated facility location problems (UFLPs) deal with the selection of facilities and assignment of customers to them. Two level UFLPs (TUFLPs) consider an additional level of facilities between the customers and the main facilities, through which the customers are connected to the production facilities. Disruption uncertainty introduces more complexity to such problems as it accounts for the probability that facilities may not always be able to satisfy the demand of their assigned customers. In this paper, we study a TUFLP with single assignment under disruption uncertainty. We investigate a two-level distribution chain, in which the flow starts from the production unit, goes through distribution centers, and then ends at the customer level. We assume a region based single commodity distribution chain whose components, excluding the customers, are prone to breakdowns due to disasters. We develop two mathematical programming formulations for the problem and develop a Tabu search algorithm and a problem specific heuristic (route subset selector - RSS), and interpret the results.